Alternation in the Degree in Rural Education - Agrarian Sciences at UFRB: student perceptions about remote activities in the pandemic - Janaine Zdebski da Silva; José Gabriel Beiginho dos Santos (Universidade Federal do Norte do Tocantins, 2024)
Presents and analyzes data collected in the network research called "Education and Rural Schools in times of Covid-19 pandemic." It takes as analytical cut the 113 online questionnaires answered, between June and July 2020, by the students of the Bachelor of Rural Education course - Agrarian Sciences of the Federal University of the Recôncavo of Bahia. The objective is to discuss possibilities/impossibilities in the construction of the alternation regime as curricular organization of the Higher Education of the working peoples of the Rural Area, of the waters and of the forests in the pandemic period, giving voice to the students. As results we have the detailed profile of the respondents of the questionnaire and their indications about the teaching of the University in that period, problematizing possibilities and impossibilities of the curriculum alternating in Higher Education of the Rural area during the pandemic of the Covid-19.